DESCRIPTION OF CHANGES IN INCREASED BODY WEIGHT IN KB PILL ACCEPTOR IN KELORARUM VILLAGE, TIKUNG SUBDISTRICT, LAMONGAN REGENCY - Mardhika, Amelia; Jayadi, Nur (Journal of Vocational Nursing, 2020)
Introduction: Hormonal contraception is one method that can be used to prevent pregnancy and plan a pregnancy. KB pills are an option because they are easy and inexpensive, but hormonal birth control has the effect of increasing body weight. The purpose of this study was to determine the description of changes in birth control acceptors' pill in Kelorarum Village, Tikung Subdistrict, Lamongan Regency. Methods: The design in this study is descriptive. The sampling technique used was consecutive sampling with a sample of 25 people collecting data with checklists, the collected data was tabulated and presented in the form of frequency tables and narratives. Results: The results in this study were acceptors who experienced changes in body weight mostly increased by 56%, acceptors with a fixed weight of 24%, while acceptors who experienced weight loss were 20%. From the original body weight. The conclusion in this study is that most acceptors experience changes in body weight. Conclusion: Based on the results of the study, it was found that most KB pill acceptors experienced changes in weight gain, and a small proportion of pill KB acceptors experienced a constant weight and weight loss.